Spectrophotometric Determination of Acidity Constant of 1-Methyl-4-[4’-aminostyryl]quinolinium Iodide in Aqueous Buffer and Micellar Solutions in the Ground and Excited States - M.A. Altalbawy, Farag; A.M. Al-Sherbini, El-Sayed (Asian Journal of Chemistry, 2013)
Electronic absorption and excitation spectra of 1-methyl-4-[4'-amino styryl]quinolinium iodide (Q-NH2) were measured in aqueous buffer and micellar solutions. The acid dissociation constants in ground and excited states, pK and pK*, were determined spectrophotometrically and amount for the aqueous solution to 3.24 and 1.19, respectively and the pK and pK* for the (Q-NH2) in sodium dodecyl sulphate are 3.72 and -1.95. The results indicated that the pks of the micellar solution is higher than that of the aqueous solution due to the concentration of protons at the micellar interface which suppress the protonation in the ground state. This reflects the large difference between the excited and the ground state dissociation constants of the micellar solution. The mechanism of the studied reactions is discussed.